A Comparison of Charge Carrier Dynamics in Organic and Perovskite Solar Cells. Issue 2 (12th November 2021) - Wu, Jiaying; Cha, Hyojung; Du, Tian; Dong, Yifan; Xu, Weidong; Lin, Chieh‐Ting; Durrant, James R.
Abstract: The charge carrier dynamics in organic solar cells and organic–inorganic hybrid metal halide perovskite solar cells, two leading technologies in thin‐film photovoltaics, are compared. The similarities and differences in charge generation, charge separation, charge transport, charge collection, and charge recombination in these two technologies are discussed, linking these back to the intrinsic material properties of organic and perovskite semiconductors, and how these factors impact on photovoltaic device performance is elucidated. In particular, the impact of exciton binding energy, charge transfer states, bimolecular recombination, charge carrier transport, sub‐bandgap tail states, and surface recombination is evaluated, and the lessons learned from transient optical and optoelectronic measurements are discussed. This perspective thus highlights the key factors limiting device performance and rationalizes similarities and differences in design requirements between organic and perovskite solar cells. Abstract : The similarities and differences in the charge carrier dynamics in organic solar cells and organic–inorganic hybrid metal halide perovskite solar cells, two leading technologies in thin‐film photovoltaics, are discussed, linking these back to the intrinsic material properties of organic and perovskite semiconductors, and how these factors impact on photovoltaic device performance is elucidated.